Causes, effects, and implications of the relationships amongst fluids, serpentinisation, and alloys - Evans, Katy; Frost, B.R.; Reddy, Steven; Brown, T.C. (2023)
Diverse assemblages of metal alloys occur within ultramafic rocks from a wide range of tectonic settings and geological environments. Alloys are typically small and can be difficult to find and identify, but they can host Re and Os, which are significant for geochronology, as well as other elements of economic interest, and can act as catalysts that help to form organic compounds. The alloys typically form from elements that show chalcophile and siderophile characteristics, indicating that alloys generally form under reducing, S-poor conditions. These conditions can be generated by a range of mechanisms that differ amongst alloy-forming environments, but include desulfidation during melting, exsolution from magmatic S-bearing phases during melt crystallisation, auto-hydrothermal, and sub-solidus processes involving a reduction in fS2, and electron transfer processes related to serpentinisation. Alloy formation during serpentinisation is typically associated with the formation of a companion phase that hosts Fe3+, such as Fe3+-bearing serpentine, magnetite, ferrit-chromite, or andradite, recording disproportionation of Fe2+ released by olivine alteration to form Fe0 and Fe3+. An additional source of electrons for alloy formation is provided by the reduction of H+ in water to H2, and the reduction of water activity couples with a reduction in fS2, driving desulfidation reactions and facilitating alloy formation. Other electron donors, such as methane, may also contribute to alloy formation. Alloy-forming serpentinites are strongly internally-buffered, but can follow a range of trajectories through compositional space. Serpentinite-hosted alloys offer opportunities to better understand a range of geological processes with applications within earth and material sciences. However, these advances require new thermodynamic data and activity composition models for all but the most common alloys, and better characterisation of alloy compositions.